Ordered carbonaceous frameworks: a new class of carbon materials with molecular-level design. Issue 22 (7th March 2022) - Yoshii, Takeharu; Chida, Koki; Nishihara, Hirotomo; Tani, Fumito
Abstract : Ordered carbonaceous frameworks are a new class of carbon materials, which comprise graphene-based three-dimensional ordered frameworks with regularly aligned single-atomic metal species. Abstract : Ordered carbonaceous frameworks (OCFs) are a new class of carbon materials with a three-dimensional ordered structure synthesized by simple carbonization of metalloporphyrin crystals with polymerizable moieties. Carbonization via solid-state polymerization results in the formation of graphene-based ordered frameworks in which regularly aligned single-atomic metals are embedded. These unique structural features afford molecular-level designability like organic-based frameworks together with high electrical conductivity, thermal/chemical stability, and mechanical flexibility, towards a variety of applications including electrocatalysis and force-driven phase transition. This feature article summarizes the synthetic strategies and characteristics of OCFs in comparison with conventional organic-based frameworks and porous carbons, to discuss the potential applications and further development of the OCF family.